Tanggung Jawab Perusahaan Internet terhadap Kelalaian Pengadaan Prasarana Kabel Utilitas (Studi Kasus PT. Bali Towerindo Sentra Tbk) - Susila, Muhamad Ipan; Fahririn, Fahririn (Universitas Batanghari Jambi, 2026)
Legal responsibility for the provision and management of utility cables in public roads has become a critical issue due to the increasing number of hanging cables that endanger road users and cause accidents. This study aims to analyze the legal liability of PT Bali Towerindo Sentra Tbk in the provision of utility cable infrastructure and to examine the forms of legal protection available to victims resulting from such negligence. The research applies an empirical or sociological legal research method using a field-based approach, supported by statutory analysis, observation, and interviews. The findings indicate that corporate liability has not been optimally enforced due to regulatory limitations, as the existing legal framework—namely the Regulation of the Minister of Public Works Number 20/PRT/M/2010 and the DKI Jakarta Governor Regulation Number 106 of 2019—only provides administrative sanctions, thereby creating a legal vacuum in terms of civil and criminal accountability. Furthermore, legal protection for victims remains inadequate, as compensation, restitution, and recovery mechanisms as stipulated under Law Number 13 of 2006 and the principles of the Indonesian Criminal Procedure Code have not been effectively implemented. This study underscores the need for specific and comprehensive regulations, as well as strengthened supervisory institutions, to ensure corporate accountability and fair legal protection for victims.